2020
DOI: 10.1186/s13058-020-01264-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-7 reduces the BCSC subset by inhibiting XIST to modulate the miR-92b/Slug/ESA axis and inhibit tumor growth

Abstract: Background: Breast cancer stem cells (BCSCs) are typically seed cells of breast tumor that initiate and maintain tumor growth. MiR-7, as a cancer inhibitor, decreases the BCSC subset and inhibits tumor progression through mechanisms that remain unknown. Methods: We examined miR-7 expression in breast cancer and developed a BCSC-driven xenograft mouse model, to evaluate the effects of miR-7 overexpression on the decrease of the BCSC subset in vitro and in vivo. In addition, we determined how miR-7 decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…qRT-PCR was performed as previously reported. 35 , 36 Briefly, RNA was extracted from each sample by using a Qiagen RNeasy Kit (Qiagen, Valencia, CA, USA). Concentration of the extracted RNA was measured with Nano Drop ND-1000 Spectrophotometer (Nano Drop Technologies, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was performed as previously reported. 35 , 36 Briefly, RNA was extracted from each sample by using a Qiagen RNeasy Kit (Qiagen, Valencia, CA, USA). Concentration of the extracted RNA was measured with Nano Drop ND-1000 Spectrophotometer (Nano Drop Technologies, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al showed that lncTCF7 was highly expressed in liver cancer stem cells (CSCs) and was important for liver CSC self-renewal [32]. [73] miR-30 promotes apoptosis [76] miR-141 promotes metastasis [74] miR-140 inhibits proliferation [77] mi-766 promotes proliferation, chemoresistance, migration and invasion [75] miR-143 inhibits proliferation [78] miR-600 inhibits stemness [79] miR-7 inhibits cell growth [80] Lung [109] miR-185 impairs survival of drug-resistant cells [110] miR-146a alleviates myeloma proliferation [111] Mechanistically, LncTCF7 recruited SWI/SNF complex to TCF7 promoter and activated Wnt signaling for sustaining liver CSC self-renewal. Epigenetically induced lncRNA1 (EPIC1) is first identified as an oncogene in luminal B breast cancer [33].…”
Section: Lncrnas In Cancersmentioning
confidence: 99%
“…In stemness-enriched cancer cells, miR-205 upregulated by NF-κB signaling suppresses COMMD1 , and then, downregulation of COMMD1 promotes intrinsic and TNF-α-induced inflammatory responses and RelA expression to maintain signaling activation [ 57 ]. RelA promotes CD44 expression but is targeted by the tumor suppressor miR-7-5p [ 58 ]. Previously, we identified that CD44 induces miR-629-3p expression and confers cisplatin resistance [ 59 ].…”
Section: Involvement Of Mirnas In Maintaining Cscsmentioning
confidence: 99%